Asymptotic behavior of solutions for a semibounded nonmonotone evolution equation - Nikos Karachalios; Nikos Stavrakakis; Pavlos Xanthopoulos (Abstract and Applied Analysis)
We consider a nonlinear parabolic equation involving nonmonotone diffusion. Existence and uniqueness of solutions are obtained, employing methods for semibounded evolution equations. Also shown is the existence of a global attractor for the corresponding dynamical system.